Pengaruh Customer Experience terhadap Loyalitas Pelanggan Melalui Brand Image dan Customer Satisfaction (Studi pada Pelanggan Warteg Sari Rasa) - Pratista, Ilham; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of customer experience on customer loyalty through brand image and customer satisfaction in Warteg Sari Rasa customers. This research uses a quantitative approach with an explanatory type of research. The population in this study were all Warteg Sari Rasa customers located in Malang City. The sample used was 85 respondents with accidental sampling technique. The data collection technique uses a questionnaire distributed via google form and has been tested for validity and reliability. The data analysis technique used is path analysis with the help of the SPSS 26 application. The results showed that: (1) Customer experience has a positive and significant effect on customer loyalty. (2) Customer experience has a positive and significant effect on brand image. (3) Customer experience has a positive and significant effect on customer satisfaction. (4) Brand image has a positive and significant effect on customer loyalty. (5) Customer satisfaction has a positive and significant effect on customer loyalty. (6) Brand image mediates the effect of customer experience on customer loyalty. (7) Customer satisfaction mediates the effect of customer experience on customer loyalty. Keywords: Customer Experience, Brand Image, Customer Satisfaction, and Customer Loyalty.